2021
DOI: 10.1080/00224499.2020.1866481
|View full text |Cite
|
Sign up to set email alerts
|

Anal Intercourse among Heterosexual Young Adults: A Population-Based Survey in Switzerland

Abstract: Anal intercourse (AI) among heterosexuals is an understudied and taboo subject. This 2017 Swiss national study aims to describe the characteristics and motivations of heterosexual young adults practicing AI. Participants with any same-sex experience, same-sex attraction or non-heterosexual identity were excluded. The Federal Statistical Office provided the initial sample and potential participants were recruited through postal mail inviting them to an online survey (response rate 15.1%). According to our resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
(64 reference statements)
0
3
0
2
Order By: Relevance
“…Further, almost 15% engaged in anal sex which, as discussed, is associated with higher STBBI transmission risk [ 48 ]. Anal sex is now considered common among young heterosexual women, associated with early sexual debut, high number of sexual partners, and intoxicated during intercourse [ 61 ]. As women face differential risks of acquiring STBBI [ 14 ], which then represents a significant threat to future fertility [ 9 , 12 ], pre-travel sexual health promotion should include comprehensive discussions of all sexual practices.…”
Section: Discussionmentioning
confidence: 99%
“…Further, almost 15% engaged in anal sex which, as discussed, is associated with higher STBBI transmission risk [ 48 ]. Anal sex is now considered common among young heterosexual women, associated with early sexual debut, high number of sexual partners, and intoxicated during intercourse [ 61 ]. As women face differential risks of acquiring STBBI [ 14 ], which then represents a significant threat to future fertility [ 9 , 12 ], pre-travel sexual health promotion should include comprehensive discussions of all sexual practices.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which the more frequent engagement in anal intercourse during the last sexual encounter indicates a difference in preference for or enjoyment of anal sexual stimulation needs to be explored in further detail, especially considering the predominating neglect of pleasure from heterosexual anal sex in existing research [32]. However, available studies found that men rated the experience of anal intercourse as significantly more pleasurable than women [33], that women had engaged in anal intercourse following their partner's request [34], pressure or coercion [35,36], and that anal intercourse in women was associated with having participated in sexual intercourse unwillingly [37,38] and with supporting views around male dominance [38]. In correspondence with the description of FGCS as a way of creating 'prototypical' genitalia to counter perceived 'abnormality' or gender ambiguity [39,40], a more frequent engagement in anal intercourse could also point to a tendency in women with FGCS to adhere to societal norms on gender and sexual agency (e.g., men being the initiators of sexual activities and women the 'gatekeepers'; or women having to cater to men's sexual 'needs' or 'entitlement' to sex).…”
Section: Discussionmentioning
confidence: 99%
“…Die in allen Kohorten hohen Raten an symptomlosen und steigenden STI-Inzidenzen weisen auf die Wichtigkeit risikoadaptierter STI-Testungen hin. Geringere Kondomnutzung, geänderte Sexualpraktiken, teils mit Chemsex, können einen Erklärungsansatz liefern [40][41][42]. Bei der Geschlechterverteilung der STI fällt auf, dass CT-und MG-Infektionen bei Männern und Frauen in der IA und 6 Die Autor*innen sehen zwischen den Kalenderjahren 2019 und 2020 einen relevanten AnstiegvonverschiedenenSTI,wobei es sichum Beobachtungen ohne statistische Auswertung handelt.…”
Section: Prep-studie Des Wirunclassified
“…Die Daten der IA weisen darauf hin, dass STI-Abstriche aus 3 Lokalisationen -oral, anal, genital -erfolgen sollten, da anderenfalls bis zu zwei Drittel der Infektionen nicht diagnostiziert werden. Da immer mehr Sexualkontakte in der Gesamtpopulation anal und oral, letztere fast immer ohne Kondom, stattfinden, ist für die Gesamtbevölkerung Aufklärung notwendig [6,[42][43][44].…”
Section: Prep-studie Des Wirunclassified